Solve communication conflict among sensor nodes in body area network. (April 2017) - Xiong, Wei; Hu, Fengye; Shao, Meiqi; Xue, Tao
Body area network is a new miniature wireless sensor network technology, which has found increasing applications, especially in medicine, healthcare, and entertainment. However, each sensor in a body area network has its own awaking and sleeping time due to its heterogeneous nature, which causes the phenomenon of communication conflict. Carrier sense multiple access with collision avoidance method could not be adopted because body area network needs real-time data transmissions, especially emergency situations. In this article, first, a body area network system with hardware, software, and network administration is designed using ZigBee technologies, which includes network structure, sensor nodes, data collection, communication with upper computer, and so on. Second, the reason caused communication conflict in the body area network is analyzed, and accordingly a method to solve the conflict problem is proposed. Finally, the feasibility and effectiveness of the proposed method is evaluated through simulation analysis and system testing.